2009
DOI: 10.1007/s00424-009-0734-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple effects of 4-aminopyridine on feline and rabbit sinoatrial node myocytes and multicellular preparations

Abstract: 4-aminopyridine (4-AP) is commonly used to block the transient outward potassium current, I(to), in cardiac and noncardiac tissues. In the present work, we found that 4-AP inhibited the rapid component of the delayed rectifier potassium current, I(Kr), in rabbit-isolated sinoatrial node myocytes by 25% (1 mM) and 51% (5 mM) and inhibited the slow component of the delayed rectifier potassium current, I(Ks), in cat- isolated sinoatrial node myocytes by 39% (1 mM) and 62% (5 mM). In cat- and rabbit-isolated sinoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 29 publications
(60 reference statements)
0
22
0
Order By: Relevance
“…As will be discussed later, block of these currents influences SA node function. In addition, 4-AP stimulates I K,Ach (Arechiga-Figueroa et al, 2010). Whether or not I to1 is present in SA node cells still remains to be resolved.…”
Section: + Current (I Cal )mentioning
confidence: 95%
See 2 more Smart Citations
“…As will be discussed later, block of these currents influences SA node function. In addition, 4-AP stimulates I K,Ach (Arechiga-Figueroa et al, 2010). Whether or not I to1 is present in SA node cells still remains to be resolved.…”
Section: + Current (I Cal )mentioning
confidence: 95%
“…In older studies 4-aminopyridine (4-AP) was used as a specific blocker for I to1 (Thompson, 1977). However, more recent studies have shown that 4-AP also blocks the www.intechopen.com ultra-rapid, rapid, and slow components of the delayed rectifier K + current (I Kur , I Kr , and I Ks , respectively) at concentrations used to analyze the role of I to1 (Li et al, 1996;Ridley et al, 2003;Arechiga-Figueroa et al, 2010). As will be discussed later, block of these currents influences SA node function.…”
Section: + Current (I Cal )mentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated SAN myocytes were obtained from adult rabbits (2-3 kg) as previously described [2]. Myocytes used for electrophysiological recordings showed spontaneous activity in the presence of normal external solution.…”
Section: Electrophysiological Recordings In Isolated Myocytesmentioning
confidence: 99%
“…Experiments were carried out on small ball-like preparations of SAN tissue from New Zealand white rabbits as previously described [2]. Intracellular action potentials were recorded using conventional glass microelectrodes (resistance, 30-40 MΩ; filling solution, 3 M KCl).…”
Section: Multicellular San Preparationsmentioning
confidence: 99%